Indonesian Language Important but Undervalued at Home: Theme and Thematic Progression Analysis - Yulia Anggraeni; Sutiono Mahdi (JEPAL (Journal of English Pedagogy and Applied Linguistics), 2020)
A text's cohesion can be seen through the thematic progression used in the text itself. Thematic progression patterns can be divided into three patterns, namely zigzag theme patterns, reiteration theme patterns, and multiple theme patterns. This research aims to analyze the thematic progression patterns in an article in The Magdalene Online Magazine. The researchers have chosen an article entitled “Indonesian Language Important but Undervalued at Home” in the Magdalene online magazine. This research used a descriptive qualitative approach. The researchers found there are sixteen zigzag theme patterns and four reiteration theme patterns in the article. The multiple theme patterns were not found in the article. The writer of the article used the zigzag thematic pattern to make cohesion in a text and introduces new information of a text, the reiteration theme pattern used when the writer tries to focus the reader about the thing that is being discussed, and the multiple theme pattern is not used because the writer does not make a Rheme becomes a number of different pieces of information in another Theme on the text.